A comparison of levels of burden in Indian and white parents with a son or daughter with schizophrenia. - Lloyd, H; Singh, P; Merritt, R; Shetty, A; Yiend, J; Singh, S; Burns, T (2011)
BACKGROUND: Caregiver burden in mental illness is believed to differ between ethnic groups, but few studies have examined this in schizophrenia in the UK. AIM: To measure burden in British North Indian Sikh and white British parents with a son or daughter with established schizophrenia managed in outpatient care. METHOD: A cross-cultural cohort study measuring family factors, patient psychopathology and levels of burden and distress. RESULTS: Overall levels of burden were low with no significant differences between the groups. Burden subscale scores showed Indian parents were more affected by psychotic behaviours than white parents. The groups also differed on several sociodemographic variables. CONCLUSION: In stabilized community patients, the overall extent of burden experienced by both Indian and white parents is low and comparable. However, Indian parents were more burdened by psychotic behaviours. This may be a result of co-residence as Indian patients are more likely to live with their families. Social and economic factors in the country of residence and levels of acculturation may also influence levels of burden and the illness behaviours found most bothersome by parents.